Farofa social: a organização social do complexo turístico em Barra Grande-PI à luz dos afetos da prática da gourmetização - Olivindo, Celina Maria de Souza (2021)
In addition to the contradictions and dichotomies seen in the relations established between society and organizations, by recounting and interpreting stories, this study intended to provide the reader with an opportunity to reflect on social, economic, environmental, and administrative issues. By investigating the phenomenon of gourmetization, this work aimed to analyze the social organization of the tourist complex of Barra Grande, on the coast of Piauí state (Brazil). Thus, it was necessary to describe the socio-material aspects of the practice of gourmetization, the perception human agents have of this practice, and gourmetization itself in Barra Grande (PI). This is a qualitative research based on the Theories of Practice. It was carried out as a sensory ethnographic and socio-material study, being supported by organizational aesthetics. Gourmetization was found to stem from three perspectives: (i) transversality, which consists of recounting, preserving, and valuing the stories of the practice; (ii) interdisciplinarity, known as inter-practice, which constitutes the link between practices; and (iii) life cycle of the practice, which represents the time of existence of the activities. As a result, the practice can promote the inclusion and exclusion of human and non-human elements. It is an organizational component, due to its power to affect places, which may be used to overcome and/or give new meanings to paradigms and dichotomies. Therefore, it was concluded that gourmetization affects the local social organization, as it generates positive and negative affections, contributing to the inclusion and/or exclusion of people, objects, cultures, etc.